Construction of beta-cyclodextrin linked glycidyl methacrylate polymers for stereoselective separation of chiral drug - Wale, Apparav; Mulani, Khudbudin; Deshpande, Supriya; Rajan, C. R.; Ponrathnam, Surendra (Journal of Polymer Research, 2021)
In this present study, a series of cross-linked porous polymers based on Glycidyl Methacrylate (GMA) were synthesized by suspension polymerization using cyclohexanol and hexanol as pore generating solvents. beta-cyclodextrin (beta-CD) was covalently bonded to the polymers by using Hexamethylene Diisocyanate (HMDI) and Sebacoyl Chloride (SC) as spacer arms. The effects of matrix properties such as pore volume, type of crosslinker, and spacer on the loading of beta-cyclodextrin were investigated. The stereoselective binding of enantiomers of the anti-depressant drug citalopram was studied using beta-cyclodextrin loaded polymers under batch adsorption mode. The capacity factor and selectivity of isomers were investigated also. This study reveals that these beta-cyclodextrin bonded Glycidyl Methacrylate (GMA) polymers are potentially suitable for chromatographic separation of citalopram.
Keywords: beta-cyclodextrin; Citalopram; Glycidyl Methacrylate (GMA) beads; HPLC etc; Stereoslelctivity